4(a+3)-2(a+6)=20

Simple and best practice solution for 4(a+3)-2(a+6)=20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(a+3)-2(a+6)=20 equation:


Simplifying
4(a + 3) + -2(a + 6) = 20

Reorder the terms:
4(3 + a) + -2(a + 6) = 20
(3 * 4 + a * 4) + -2(a + 6) = 20
(12 + 4a) + -2(a + 6) = 20

Reorder the terms:
12 + 4a + -2(6 + a) = 20
12 + 4a + (6 * -2 + a * -2) = 20
12 + 4a + (-12 + -2a) = 20

Reorder the terms:
12 + -12 + 4a + -2a = 20

Combine like terms: 12 + -12 = 0
0 + 4a + -2a = 20
4a + -2a = 20

Combine like terms: 4a + -2a = 2a
2a = 20

Solving
2a = 20

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Divide each side by '2'.
a = 10

Simplifying
a = 10

See similar equations:

| X^2+5x=1500 | | -8(6k-8)=-272 | | 5x^4-6x=109 | | 3(y-1)+2(y+3)=13 | | 8g+4h=68 | | x^4-2x^3+x^2-12x=0 | | 8+9(9+8w)= | | 7x^2-245x=0 | | 3x+(11-x)=11 | | x-lnx(2x)=0 | | 17=13+4 | | 3x+5+4x=19 | | 6(x+2)-4x=30 | | 4+13=-17 | | 6(4x-12)=8x+9 | | 13+4=-17 | | x^3-7x^2-6x-1=0 | | 4y+2(y-2)=8 | | 2x+(1-x)=4 | | 2y+6(y+3)=32 | | 52*500= | | 9x+1+7x+3=180 | | 2z+5y=8 | | X+8(x+2)=52 | | (2x*2x)+(5x+13)*(5x+13)=(6x+8)*(6x+8) | | -4+5(5r+6)=-49 | | 2x+3xy= | | 8+8(4x+5)=-48 | | 10r+3(-1+10r)= | | 3n+4(4n+4)=-22 | | 6x^2-24x+9=0 | | 4(2x+5)=2(3x-2) |

Equations solver categories